(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
تم استخدام مطيافية الإصدار الضوئي التجاوبي لاختبار مساهمة الكترونات Co 3d و Tb 4f إلى البنية الالكترونية لعصابة التكافؤ في البلورة TbBaCoO3. وتم قياس تجاوب نوع فانو بطاقة إشعاع لتطابق الانتقالات الضوئيةCo 3p→3d و Tb 4d→4f. وتم تحديد منحنيات توزيع الطاقة المطابقة لعصابة تكافؤ البلورة من أجل طاقة إشعاع hv عند 60eV (التجاوب Co 3p→3d) و155eV (التجاوب Tb 4d→4f ). وجدت المساهمة الرئيسية من إلكترونات Co3d المشاركة في القمة الرئيسية عند طاقة 5.5 eV تحت حافة عصابة التكافؤ. كما لوحظ مساهمة من إلكترونات Tb 4f عند طاقة9.3 eV تحت حافة عصابة التكافؤ. Resonant Photoemission Spectroscopy was used to investigate the contribution of Co3d and Tb4f electrons to the electronic structure of the valence band of TbBaCoO3 crystal. The Fano type resonance tuned to the Co 3p→3d and Tb 4d→4f transitions was measured. The Energy Distribution Curves corresponding to the valence band of the crystal were determined for radiation energies hv in the region of 60eV (Co3p→3d resonance) and 155eV (Tb4d→4f resonance). The main contribution of Co 3d electrons was found in the main valence band peak located at 5.5 eV below the valence band edge. The contribution of Tb4f electrons was found at the binding energy 9.3 eV below the valence band edge.